Translation, validation and cross-cultural adaptation of the Malay emotion regulation checklist (ERC-M): A preliminary study - Jamal, Fatin Nabilah; Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Musa, Ramli (Malaysian Medical Association, 2021)
Introduction: Emotion Regulation Checklist (ERC) has been used globally and translated to several languages, including Brazilian Portuguese, Italian and Persian. The aim of this study is to translate and validate ERC to the Malay language and to measure the reliability and validity of the translated version of this scale among Malaysian parents. Methods: This study involved forward and back translation method. The translated questionnaire was then pretested and piloted among 10 parents and 50 participants, respectively. The procedure was repeated using the same questionnaire to evaluate the test-retest reliability. Results: The ERC-Malay (ERC-M) has excellent qualitative and quantitative measurements in both item-level content validation index (I-CVI) and scale-level content validation index (S-CVI). In addition, the ERC-M demonstrated good internal consistency from Cronbach’s alpha and test-retest reliability based on the Intraclass Correlation Coefficient (ICC) in all domains. Conclusion: ERC-M can potentially be used as a tool to evaluate emotion for the population with emotional dysregulation issue, such as autism spectrum disorder.